Treatment of locoregional recurrent colon cancer - Handtrack, Claudia; Weber, Klaus; Merkel, Susanne; Grützmann, Robert; Denz, Axel (Coloproctology, 2022)
The local recurrence rate of colon cancer could be markedly reduced after complete mesocolic excision (CME) criteria were implemented in oncological surgery. Risk factors for local recurrence include incomplete resection as well as the site of the primary tumor and locally or lymph node advanced tumors (pT4/pN2). Further risk factors are emergency operations and postoperative complications, particularly anastomotic leakage. The outcome of local recurrent colon cancer is decisively influenced by the resectability. In cases of a curative R0 resection, possibly including neoadjuvant therapy or multivisceral resections, a 5-year survival rate of over 50% can be achieved.
CRIS-Team WoS Importer:2022-05-27
Keywords: Colorectal cancer; Local recurrence; R0 resection; Staging; Prognosis